Partial revision of the exclusively Neotropical species of Zelia Robineau-Desvoidy, 1830 (Tachinidae: Dexiinae: Dexiini), with the description of a new species - Santis, Marcelo Domingos De; O’hara, James E.; Couri, Márcia Souto (Zootaxa, 2024)
Zelia Robineau-Desvoidy, 1830 is a genus of Dexiini distributed throughout the New World, with most of its species in the Neotropical Region. This revision deals with the exclusively Neotropical species of Zelia, with the exception of the recently revised Zelia discalis group. The following new synonyms of Zelia are proposed in the present study: Diaugia Perty, 1833, syn. nov.; Huascarodexia Townsend, 1919, syn. nov.; Taperamyia Townsend, 1935, syn. nov.; Ushpayacua Townsend, 1928, syn. nov.; and Yahuarmayoia Townsend, 1927, syn. nov.. As a result of these synonymies, the following new combinations are proposed: Zelia angusta (Perty, 1833), comb. nov.; Zelia pickeli (Townsend, 1938), comb. nov.; Zelia pulchra (Townsend, 1919), comb. nov.; and Zelia ureophila (Townsend, 1928), comb. nov. Two additional species are moved to Zelia from other genera: Zelia obscura (Walker, 1853), comb. nov. (from Stomatodexia Brauer & Bergenstamm, 1889); and Zelia varipennis (Wulp, 1891), comb. nov. (from Scotiptera Macquart, 1835). Additionally, Melaleuca peruviana Brèthes, 1920 is moved from its placement in Zelia to “Unplaced species of Tachininae”. Illustrations and detailed descriptions are presented for all species dealt with here. The male terminalia are described for Z. obscura, Z. pickeli and Z. potens. The female terminalia are described for the first time for Z. limbata, Z. pickeli, Z. plumosa, Z. potens and Z. ureophila. The first larval instar of Z. limbata, Z. pickeli, Z. plumosa and Z. potens are described and illustrated for the first time. A new species, Zelia infuscata sp. nov., is described from Brazil. Two new synonyms are proposed at the species level: Yahuarmayoia analis Townsend, 1927 (type species of Yahuarmayoia) and Yahuarmayoia phaeoptera (Wiedemann, 1830) as junior synonyms of Zelia potens (Wiedemann, 1830), syn. nov. Zelia phaeoptera is recognized as a subjective synonym of Z. potens, and by First Reviser action, the latter is chosen as the senior of the two Wiedemann names. An updated diagnosis for the genus Zelia and a key to the Neotropical species, including the Nearctic species that also occur in the Neotropics, are given. Previous lectotype fixations are recognized for Dexia limbata Wiedemann, 1830 and Dexia phaeoptera Wiedemann, 1830, and new lectotype designations are proposed for Dexia obscura Walker, 1853, Dexia plumosa Wiedemann, 1830 and Dexia potens Wiedemann, 1830. Finally, a brief biography of Dom Bento Pickel, who collected the holotype of Z. pickeli, is given.